Hubungan Kesediaan Berkomunikasi dengan Kecemasan Berbicara Bahasa Arab - Intiha Bima Tafriha; Maslamah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the relationship between willingness to communicate (WTC) and Arabic speaking anxiety among ninth-grade students of MTs Negeri 4 Karanganyar. The background of the study arises from the finding that Arabic speaking skills are often hindered by language anxiety, which affects students' participation in classroom communication activities. This study uses a quantitative approach with a survey technique. Data collection instruments include the Willingness to Communicate Scale (McCroskey, 1992) and the Public Speaking Anxiety Scale (PSAS) to measure speaking anxiety. The research sample consisted of 61 students, obtained through a random sampling technique based on Slovin's formula from a population of 155 students. Data analysis was conducted using the Pearson product-moment correlation to examine the strength of the relationship between variables. The results showed a significant negative correlation between willingness to communicate and anxiety in speaking Arabic (r = –0.893; p < 0.05). These findings indicate that the higher the students' willingness to communicate, the lower the level of speaking anxiety they experience. An R Square value of 0.798 shows that willingness to communicate contributes 79.8% to Arabic speaking anxiety, while the remainder is influenced by factors beyond this study. Overall, this research confirms that strengthening willingness to communicate plays an important role in reducing Arabic-speaking anxiety. The implications of this study emphasize the need for learning strategies that encourage bravery, provide broader speaking opportunities, and create a non-threatening classroom environment so that students are more active in communication practice.